Realizace terénní práce v sociálně vyloučených lokalitách na příkladu města Pardubice - Flosman, Radek (Univerzita Pardubice, 2008)
Socially excluded locality fieldwork belongs among the unreplaceable parts of the fundamental social services. This kind of services has been carrying out since 2002 and on the basis of successful results its extent is considering in these days. The article refers to the issue regarding fieldwork from the point of view of municipality as an executor. The author focuses on several key fields more in detail. It particularly deals with effective application of the services, a way how to keep it and also its funding. The author´s subjective remarks and experiences taken from his job as a field worker in socially excluded localities in Pardubice become a part of the article.
Keywords: streetwork; social services; social exclusion; problematic areas; social inclusion